Erythrodermic psoriasis: pathophysiology and current treatment perspectives - Singh RK; Lee KM; Ucmak D; Brodsky M; Atanelov Z; Farahnik B; Abrouk M; Nakamura M; Zhu TH; Liao W (Dove Medical Press, 2016)
Rasnik K Singh,1 Kristina M Lee,2 Derya Ucmak,2 Merrick Brodsky,3 Zaza Atanelov,4 Benjamin Farahnik,5 Michael Abrouk,3 Mio Nakamura,2 Tian Hao Zhu,6 Wilson Liao2 1Department of Medicine, University of California – Los Angeles, David Geffen School of Medicine, Los Angeles, 2Department of Dermatology, University of California – San Francisco, San Francisco, 3Department of Medicine, University of California – Irvine, School of Medicine, Irvine, CA, 4Department of Medicine, New York Medical College, Valhalla, NY, 5Department of Medicine, University of Vermont College of Medicine, Burlington, VT, 6Department of Medicine, University of Southern California Keck School of Medicine, Los Angeles, CA, USA Abstract: Erythrodermic psoriasis (EP) is a rare and severe variant of psoriasis vulgaris, with an estimated prevalence of 1%–2.25% among psoriatic patients. The condition presents with distinct histopathologic and clinical findings, which include a generalized inflammatory erythema involving at least 75% of the body surface area. The pathogenesis of EP is not well understood; however, several studies suggest that the disease is associated with a predominantly T helper 2 (Th2) phenotype. Given the morbidity and potential mortality associated with the condition, there is a need for a better understanding of its pathophysiology. The management of EP begins with a comprehensive assessment of the patient’s presentation and often requires multidisciplinary supportive measures. In 2010, the medical board of the US National Psoriasis Foundation published consensus guidelines advocating the use of cyclosporine or infliximab as first-line therapy in unstable cases, with acitretin and methotrexate reserved for more stable cases. Since the time of that publication, additional information regarding the efficacy of newer agents has emerged. We review the latest data with regard to the treatment of EP, which includes biologic therapies such as ustekinumab and ixekizumab. Keywords: erythrodermic psoriasis, EP, pathogenesis, pathophysiology, treatment, biologics